Preparedness of Dammam primary health care centers to deal with emergency cases - Sanaa S. M Alsaad; Salma H. S Abu-Grain; Dalia Y. M El-Kheir (Wolters Kluwer Medknow Publications, 2017)
OBJECTIVES: The objective of the study was to assess the availability of human and nonhuman resources for emergency medical services (EMSs) at the primary health care (PHC) level. MATERIALS AND METHODS: A cross-sectional study with mixed research methods (quantitative and qualitative) was carried out in governmental PHC centers in Dammam, Eastern Province of Saudi Arabia, between September 2014 and January 2015. Using systematic random sampling technique, 13 out of 26 PHC centers were included in the study. The study consisted of two main parts: The first involved the completion of an observational checklist to assess the availability and adequacy of human and nonhuman resources (workforce, emergency infrastructure, equipment, drugs and supporting facilities). The second part involved face-to-face interviews with key informants of nurses from the emergency room (ER) in the sampled centers. RESULTS: Analysis of the checklist showed that the total number of physicians "actually" present ranged from 2 to 8 per center and nurses actually present were 4-11 whereas the officially assigned number was 3-12 physicians and 8-17 nurses per center. Only 2 out of 13 (15.4%) centers had a place reserved for EMS in each male and female section. Only 4 (30.8%) PHC centers had a male ER located on the ground floor, near the entrance, and with a separate ramp. None of the centers had the emergency drugs such as metergotamine, calcium chloride, and naloxone. Regarding ER equipment, none of the studied centers had cervical collars, mouth gags, or a tracheostomy sets. Only one (7.6%) center had a functioning fully equipped ambulance. Five (38.46%) centers were equipped with electrocardiogram and X-ray machines. In the interviews, the informants confirmed the deficiencies identified in the checklist. CONCLUSION: Resources for EMS at Dammam PHC centers were deficient in infrastructure and supporting facilities.